Promoting green transformation of enterprises in China to adapt to climate change: an evolutionary game analysis - Luo, Jin; Feng, Wei (Frontiers in Climate, 2025)
Climate change is driving the traditional development mode to a green, low-carbon, and sustainable development path. Enterprise green transformation is an important path to achieve green and low-carbon. This study, based on evolutionary game theory, analyzes the driving mechanisms of enterprises green transformation, focusing on the interactive relationship between government policy support and enterprise green transformation. By constructing a game model for both government and enterprises, it examines the impacts of different levels of policy support, enterprise transformation costs, market return expectations, and environmental penalties on enterprise green transformation decisions. The results indicate that high government policy support significantly enhances the success rate of enterprise green transformation, while transformation costs, market returns, and environmental penalties play important moderating roles in the decision-making process. Particularly in the context of the “dual carbon” goals, sustained and stable policy support is crucial for enterprise green transformation. This study further suggests promoting enterprise green transformation through market-oriented measures, digital technology empowerment, and long-term incentive mechanisms, providing theoretical foundations and practical guidance for government policy formulation and enterprise green development.